Efektivitas Pelayanan Pendaftaran Online Bagi Pengguna Mobile JKN Di Klinik Pusdikarhanud - Radha Ardya Garini Putri Tarika; Lilik Afifah; Agus Syukron Ma'ruf (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
Digital transformation in the health sector has encouraged the use of the Mobile JKN application as an online patient registration service. However, in practice, several technical problems and differences in user acceptance are still found. This study aims to analyze the effectiveness of online registration services through Mobile JKN at Pusdikarhanud Clinic using the End User Computing Satisfaction (EUCS) method, which consist of five dimensions: content, accuracy, format, ease of use, and timeliness. This study employed a descriptive qualitative approach with data collected through interview, observation, and document studies. The informants included the head of the clinic, medical record officers, and six patients grouped into three age ranges. The results show that Mobile JKN improves service efficiency and accelerates the registration process, especially in the ease of use and timeliness dimension. However, problems were still found in the content dimension related to data completeness, in the accuracy demension related to confirmity with official identity documents, and in the format dimension related to integration with the Electronic Medical Record system. In addition, age factors influence user experience and satisfaction. Overall, Mobile JKN is considered effective, but technical improvements and better system integration are still needed.